Optimization of process conditions for catalytic alkylation of isomeric cresols with cyclohexene (Bangladesh Journal of Scientific and Industrial Research, 2012)
Alkylation of isomeric cresols with cyclohexene in presence of perchloric acid as catalyst was studied and cyclohexyl cresols obtained in high yield. The effects of the variation of reaction parameters such as temperature, molar ratio of cresol to cyclohexene, amount of perchloric acid and time of reaction were investigated. The yield of the products increased with the increase of each of the above-mentioned parameters. Optimum yield (97.6% for cyclohexyl m-cresol; 95.4% for 2-cyclohexyl-4-methylphenol and 91.2% for cyclohexyl o-cresol) of the products were obtained under the reaction conditions of a temperature of 140ºC; an 8-6:1 molar ratio of cresol to cyclohexene, a 5% by weight perchloric acid of cresol, a 2 h time of addition of cyclohexene and a 2 h time of stirring of the reaction mixture. Considering the yields of cyclohexyl cresols and ease of purifications, the above mentioned conditions were accounted as optimum for the alkylation of isomeric cresols with cyclohexene in the presence of perchloric acid.   DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11446   Bangladesh J. Sci. Ind. Res. 47(2), 153-160, 2012